2008
DOI: 10.1051/0004-6361:200810272
|View full text |Cite
|
Sign up to set email alerts
|

Progenitor mass of the type IIP supernova 2005cs

Abstract: Context. The progenitor mass of type IIP supernova can be determined from either hydrodynamic modeling of the event or preexplosion observations. Aims. To compare these approaches, we determine parameters of the sub-luminous supernova 2005cs and estimate its progenitor mass. Methods. We compute the hydrodynamic models of the supernova to describe its light curves and expansion velocity data. Results. We estimate a presupernova mass of 17.3 ± 1 M , an explosion energy of (4.1 ± 0.3) × 10 50 erg, a presupernova … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
131
7
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(158 citation statements)
references
References 34 publications
13
131
7
7
Order By: Relevance
“…7a) and the total 56 Ni mass versus the progenitor mass (Fig. 7b) strengthens the correlations recovered earlier for the SNe IIP studied hydrodynamically (Utrobin & Chugai 2008). We note that these correlations also infer the correlation between the explosion energy and the total 56 Ni mass, which was found and discussed earlier by Nadyozhin (2003).…”
Section: Progenitor Masssupporting
confidence: 90%
See 1 more Smart Citation
“…7a) and the total 56 Ni mass versus the progenitor mass (Fig. 7b) strengthens the correlations recovered earlier for the SNe IIP studied hydrodynamically (Utrobin & Chugai 2008). We note that these correlations also infer the correlation between the explosion energy and the total 56 Ni mass, which was found and discussed earlier by Nadyozhin (2003).…”
Section: Progenitor Masssupporting
confidence: 90%
“…We adopt the pre-SN model with an envelope mass of 15.9 M and a density distribution that closely resembles that of the evolutionary model (Utrobin & Chugai 2008). The hydrogen and helium are assumed to be mixed along the mass coordinate in a similar way to the optimal model (Fig.…”
Section: Explosion Of Evolutionary Presupernovamentioning
confidence: 99%
“…Pastorello et al (2009) analyzed an extensive data set to estimate M 10 ZAMS » -15 M  by a semi-analytic fit of the data to the model of Zampieri et al (2003). Finally, Utrobin & Chugai (2008), with radiation-hydrodynamics modeling, obtain a larger M ZAMS of 17.2-19.2 M  . Interestingly, if this latter estimate is correct there would be a strong implication that sub-luminous SNe II arise from two distinct progenitor populations, a low-mass (∼7-10 M  ) population and a relatively high-mass (20 M  ) population.…”
Section: Observational Samplementioning
confidence: 99%
“…This requires corrections for estimated mass loss during progenitor evolution and a compact remnant mass estimate. Since this method requires high-quality photometric and spectroscopic data, it has only been applied to a handful of events where such data are available (e.g., Zampieri et al 2003;Baklanov et al 2005;Utrobin 2007;Utrobin & Chugai 2008, 2009Pastorello et al 2009;Dall'Ora et al 2014). Typically, these models of explosions in RSGs predict significantly higher ZAMS masses than those obtained by direct imaging.…”
Section: Introductionmentioning
confidence: 99%
“…SN 2005cs seems to belong to the subtype of low-luminosity, 56 Ni-poor, low-velocity SNe II-P, as shown also by long-term studies of Tsvetkov et al (2006;optical photometry), Gnedin et al (2007; R-band photometry and polarimetry), and Pastorello et al (2009;optical and near-IR photometry, optical spectroscopy). Extensive studies of the first-year data and pre-explosion images resulted in a progenitor mass of 7−13 M (Maund et al 2005;Li et al 2006;Takáts & Vinkó 2006;Eldridge et al 2007), while Utrobin & Chugai (2008) determined a significantly higher value (17−19 M ). In their more recent work Pastorello et al (2009) concluded that the progenitor mass should be in the range of 10−15 M .…”
Section: Supernova Sample Observed By Spitzermentioning
confidence: 99%